Развојна дисхармонија од психотичен тип согледана од невропсихолошки аспект - Копачев, Драгослав; Трајковски, Владимир; Ајдински, Горан (Faculty of Philosophy, UKIM, Skopje, Macedonia, 1998)
Based on a case from the clinical praxis, the authors, adopting a neuropsyhological attitude, study and define the developmental disharmony of a psychotic type. They consider that the developmental disharmony of a psychotic type represents a global and profound destruction of structures and functions (motors, speech, emotions, cognition, socialization). The foundation thesis is that in basic of the disharmony developmental structure of the child. A “psychotic nucleus” is being created rather early in the age of Child’s development, with under pressure of the no favorable environmental factors leads to psychotic manifestation of the personality. The developmental disharmony of a psychotic type could have a various outcome. The child could manifest a progressive intellectual deterioration, to evolve in a direction of schizophrenic psychoses, to structure itself as a “Borderline” personality, while very rarely a relative normalization of the personality could occur. The authors promote the significance of early detection, qualitative diagnostics and adequate treatment by well educated and polyvalent, multidisciplinary expert team.
Developmental Disharmony of Psychotic Type Overview from a Neuropsychological Aspect
Keywords: развојна дисхармонија, психоза, невропсихологија